Information Support Technology of Ship Survey Based on Case-based Reasoning - Jiyin Cao; Shidong Fan; Wen Lu; Haiyun Liu (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2014)
Recently, the significance of ship inspections hasbeen increasingly recognized because sea pollution andsafety problems are occurring more and more frequently. However, current ship inspections rely on the experience ofthe workers. Therefore, it is difficult to understand, and hence to improve, the state of ship inspections. The present problemsare that the ship inspection technical support level in China is not balanced, especially as to the current situation with low level, poor technologyin under-developed areas. In this paper, the case technology about the case-based reasoning to the ship inspection is proposed. The methods of normative inspection case representation are discussed.This is considered to be the basis of case-based reasoning. Then the tertiary case structure with the index is defined, in which the K-nearest neighbor method to calculate the similarity between caseswas used so that the ship’s inspection information can be searched effectively. In addition, animproved retrievalstrategy of the nearest neighbor method is introduced. Therefore, in the inspection site,the inspectors can acquire support information by the case bases, and then the new cases are calculated automatically. Further, a ship inspection case managementwereintroduced to improve the stability of the system. By carrying the case-based reasoning into an inspection, an inspector can generate fault information and inspection information simply and easily. Some examples of the organization and retrieval are shown at the end of the paper.